Evaluation of the Accuracy of Working Length Determination Using Cone-Beam Computed Tomography, Digital Periapical Radiography and Electronic Apex Locator: An In-vitro Study (Journal of Hama University, 2024)
Introduction: The purpose of this in-vitro study was to compare the accuracy of working length (WL) determination using three demotions (3D) cone-beam computed tomography (CBCT), 2-demotions digital periapical radiographies (2D) and electronic apex locator (EAL). Methods and Materials: A total of 40 human extracted single-rooted teeth were chosen. Access cavity was performed, and actual root canal lengths were measured. Then, a file was advanced into the canal until the WL was detected by digital radiography. Subsequently, the WL was measured using EAL, and CBCT. These three measurements were compared and the data were analyzed using the T-student test. The level of significance was set at 0.05. Results: The mean values for WL determination differences using electronic apex locator, periapical radiograph and CBCT images were not statistically significant (P>0.05). Conclusion: The accuracy of working length determination using 3D images was equal to electronic apex locator and digital radiographic at least with two different angels.
Keywords: working length; digital radiographies; electronic apex locator; CBCT